1988
DOI: 10.1002/pi.4980200306
|View full text |Cite
|
Sign up to set email alerts
|

D.s.c., electrical conductivity, and n.m.r. studies of salt precipitation effects in PPO complexes

Abstract: Differential scanning calorimetry (d.s.c.) and electrical conductivity measurements of poly(propylene oxide), PPO, complexed with the salts NaI and KSCN are reported. In addition, 23Na n.m.r. measurements on PPO‐NaI (x = 8), both at ambient and elevated pressure (2 kbar), have been performed. The d.s.c. data clearly indicate that the salt precipitates out of the complexes at about 85°C for NaI and 60°C for KSCN. These effects are manifested by a dramatic departure of the conductivity from Vogel‐Tammann‐Fulcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Two studies deal with SP in the PPO-KSCN system [10,11]. Teeters et al [11] investigated SP as a function of salt concentration in PPO complexed with NaSCN or KSCN and found a monotonic decrease of the SP onset temperature with increasing cation-to-oxygen ratio.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Two studies deal with SP in the PPO-KSCN system [10,11]. Teeters et al [11] investigated SP as a function of salt concentration in PPO complexed with NaSCN or KSCN and found a monotonic decrease of the SP onset temperature with increasing cation-to-oxygen ratio.…”
Section: Introductionmentioning
confidence: 98%
“…Most early reports on SP in polymer electrolytes concern PPO that was complexed with sodium salts to a fixed O/Na ratio of (or close to) 8, including NaClO 4 [6], NaI [7,10], and NaSCN [7,8,11]. Two studies deal with SP in the PPO-KSCN system [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 ,7,8 In fact, it has been found that in some complexes (PPO-NaI and PPO-KSCN) the electrical conductivity, instead of increasing, begins to drop above some critical temperature if the samples are equilibrate long enough. 8 The equilibrium time was then attributed to the time needed for the salt to precipitate at a certain temperature. In the case of sodium salts it has been shown that the precipitation temperature increases as the concentration decreases and as the melting point of the dopant salt decreases.…”
Section: Introductionmentioning
confidence: 99%